Isotherm And Kinetics Of Reactive Dye Adsorption On Palm Kernel Shell-Based Activated Carbon - Mobarekeh, Mohsen Nourouzi (2007)

(untitled)
The adsorptions of two reactive dyes, Reactive Black 5 and Reactive Red E onto Palm Kernel Shell-based activated carbon (granule form) and commercial grade coal-based activated carbons (powder form) were studied. The experiment was carried out to investigate the effect of the presence of more than one type dye in solution on equilibrium and kinetic of adsorption. Equilibrium isotherm models were applied to describe the adsorption capacities of both single and binary systems. All batch experiments were carried out at a constant temperature of 28°C (+2°C) using an incubator shaker that was operated at 150 rpm. The results showed that adsorption of reactive dyes onto commercial coal-AC from single system can be successfully described by Langmuir model. The adsorptions onto Palm Kernel Shell-AC in single and binary systems can be successfully described by Freundlich and the Redlich-Peterson models and by Modified Extended Freundlich model, respectively. Experimental data showed that competitive adsorption for active sites on the carbon surface reduces overall uptake capacity of the reactive dyes. The rate of adsorptions of two reactive dyes, Reactive Black 5 and Reactive Red E onto Palm Kernel Shell-AC were studied. The sorption kinetics was well described by pseudo-second-order kinetic model in single system. In addition, the experiment was carried out to investigate three models: film resistance model, film-surface and film-pore diffusion models. The results showed that the external coefficients of mass transfer, Kf, decreased with increasing of initial adsorbate concentration. Variations of Kf values, indicated that adsorption was controlled by both external and intraparticle diffusion. Furthermore, simulation results showed that the rate of the kinetic process was controlled by two resistance models. It was found that the adsorption process was better described by film-surface diffusion model. Finally, the Chemical Oxygen Demand (COD) of the treated reactive dyes solutions from single and binary systems showed that a minimum of 4g/L dosage of PKS was needed to reduce the COD to acceptable level according to the United State Water Quality Guidelines and Pollutant Fact Sheets guidelines. From the work, it was clearly shown that PKS-AC had good adsorption capacity on reactive dye. This study provides information on adsorption mechanism of binary reactive dye system which is useful in adsorption column design